2020
DOI: 10.1534/g3.120.401125
|View full text |Cite
|
Sign up to set email alerts
|

Validation of QTLs for Fiber Quality Introgressed from Gossypium mustelinum by Selective Genotyping

Abstract: Gene introgression from wild species has been shown to be a feasible approach for fiber quality improvement in Upland cotton. Previously, we developed an interspecific G. mustelinum × G. hirsutum advanced-backcross population and mapped over one hundred QTL for fiber quality traits. In the current study, a trait-based selective genotyping approach was utilized to prioritize a small subset of introgression lines with high phenotypic values for differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…By comparing the physical confidence interval of QTLs in different studies, 35 stable QTLs in this work were found sharing overlapped interval with previous reported QTL (Supplementary Table 11), and 15 of them were detected in more than one previous work. Among them, qFL_A10.3 was found to be the same with QTLs in other five works (Liang et al, 2013;Shao et al, 2014;Wang H. et al, 2016;Shi et al, 2019), and qFL_D11.1 and qLP_D03.1 were found to be the same with QTLs in other four works, respectively (Wang et al, , 2020Ning et al, 2014;Shi et al, 2015;Jamshed et al, 2016;Diouf et al, 2018;Ma J. et al, 2018). Six QTLs (qFE_D02.3, qFL_A08.5, qFL_D07.1, qFL_D13.3, qFS_D01.1, qFS_D07.1) were identified in other three previous works (Shen et al, 2006;Feng et al, 2015;Tang et al, 2015;Wang F. et al, 2016;Zhang et al, 2016).…”
Section: Major Quantitative Trait Loci Clusters and Common Quantitative Trait Loci Reveal Footprints Of Cotton Domesticationmentioning
confidence: 59%
See 1 more Smart Citation
“…By comparing the physical confidence interval of QTLs in different studies, 35 stable QTLs in this work were found sharing overlapped interval with previous reported QTL (Supplementary Table 11), and 15 of them were detected in more than one previous work. Among them, qFL_A10.3 was found to be the same with QTLs in other five works (Liang et al, 2013;Shao et al, 2014;Wang H. et al, 2016;Shi et al, 2019), and qFL_D11.1 and qLP_D03.1 were found to be the same with QTLs in other four works, respectively (Wang et al, , 2020Ning et al, 2014;Shi et al, 2015;Jamshed et al, 2016;Diouf et al, 2018;Ma J. et al, 2018). Six QTLs (qFE_D02.3, qFL_A08.5, qFL_D07.1, qFL_D13.3, qFS_D01.1, qFS_D07.1) were identified in other three previous works (Shen et al, 2006;Feng et al, 2015;Tang et al, 2015;Wang F. et al, 2016;Zhang et al, 2016).…”
Section: Major Quantitative Trait Loci Clusters and Common Quantitative Trait Loci Reveal Footprints Of Cotton Domesticationmentioning
confidence: 59%
“…A total of 72 stable QTLs were identified, and many of them had been reported in previous studies ( Shen et al, 2005 , 2019 ; Zhang et al, 2011 ; Su et al, 2013 ; Yu et al, 2013 ; Shang et al, 2015 , 2016 ; Guo et al, 2018 ; Deng et al, 2019 ; Ma et al, 2019 ; Chen et al, 2020 ). By comparing the physical confidence interval of QTLs in different studies, 35 stable QTLs in this work were found sharing overlapped interval with previous reported QTL ( Supplementary Table 11 ), and 15 of them were detected in more than one previous work.…”
Section: Discussionmentioning
confidence: 99%
“…The historical domestication and modern breeding of Upland cotton ( Gossypium hirsutum ) have significantly improved its yield and fiber quality, but this has led to a dramatically reduced genetic diversity [ 24 , 25 , 26 , 27 ]. Upland cotton cultivars have a narrow genetic base of fiber quality and abiotic stress tolerance traits.…”
Section: Introductionmentioning
confidence: 99%
“…The fiber of G. mustelinum is genetically different from that of allotetraploid G. hirsutum . The quantitative trait loci (QTL) for fiber quality and the interesting alleles identified from G. mustelinum can make an important contribution to the improvement of Upland cotton germplasm [ 25 ]. Wang et al [ 30 ] dissected the molecular genetic basis of fiber strength and fineness in G. mustelinum and G. hirsutum crosses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation